Preventing childhood scalds within the home: overview of systematic reviews and a systematic review of primary studies - Zou, Kun; Wynn, Persephone M.; Miller, Philip; Hindmarch, Paul; Majsak-Newman, Gosia; Young, Ben; Hayes, Mike; Kendrick, Denise (Elsevier, 2015)
Objective: To synthesise and evaluate the evidence of the effectiveness of interventions to prevent scalds in children. Methods: An overview of systematic reviews (SR) and a SR of primary studies were performed evaluating interventions to prevent scalds in children. A comprehensive literature search was conducted covering various resources up to October 2012. Experimental and controlled observational studies reporting scald injuries, safety practices and safety equipment use were included. Results: Fourteen systematic reviews and 39 primary studies were included. There is little evidence that interventions are effective in reducing the incidence of scalds in children. More evidence was found that inventions are effective in promoting safe hot tap water temperature, especially when home safety education, home safety checks and discounted or free safety equipment including thermometers and thermostatic mixing valves were provided. No consistent evidence was found for the effectiveness of interventions on the safe handling of hot food or drinks nor improving kitchen safety practices. Conclusion: Education, home safety checks along with thermometers or thermostatic mixing valves should be promoted to reduce tap water scalds. Further research is needed to evaluate the effectiveness of interventions on scald injuries and to disentangle the effects of multifaceted interventions on scald injuries and safety practices.